The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/md.0000000000020412
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of stone recurrence after endoscopic retrograde cholangiopancreatography for common bile duct stones

Abstract: To explore the risk factors related to the recurrence of common bile duct stones (CBDS) after endoscopic retrograde cholangiopancreatography (ERCP), so as to provide reference for reducing the recurrence of CBDS after ERCP. The clinical data of 385 patients with CBDS treated by ERCP from March 2012 to May 2016 were collected. According to the diagnostic criteria of recurrence of CBDS, the patients were divided into recurrence group and control group. The general information of the patients, personal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Gupta et al [ 24 ] also found that ERCP involved more reinterventions than one-stage treatment of bile duct stones. Laparoscopic CBDE also reduces the incidence of recurrent stones, thus avoiding inevitable future reinterventions [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al [ 24 ] also found that ERCP involved more reinterventions than one-stage treatment of bile duct stones. Laparoscopic CBDE also reduces the incidence of recurrent stones, thus avoiding inevitable future reinterventions [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, endoscopic retrograde cholangiopancreatography (ERCP) remains the effective and minimally invasive treatment option for bile duct stone ( Cianci and Restini, 2021 ). However, the relapse rate of bile duct stone is still high, up to 4-24% within 3-5 years, which can lead to patients’ suffering, increased medical expenditure, and risk of cholangiocarcinoma ( Lujian et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 1.5% of the general population suffers from CBD stone, and the prevalence increases with age. [ 8 ] In fact, CBD stone spectrum of clinical presentations ranges from mild disease including biliary colic and abnormal liver enzymes to the more severe and life-threatening diseases, including pancreatitis, cholangitis, and sepsis, which can deteriorate and lead to death. In our study, and for the first time, we identified that DM significantly correlated with acute cholangitis among patients with CBD stone on univariate and multivariate analysis with OR of 1.93 (95% CI 1.26–2.96).…”
Section: Discussionmentioning
confidence: 99%